The Utilization of Herbal Plants for Hypertension Patients in Langsa City Aceh Province - Diza Fathamira Hamzah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Langsa City is one of the region in Aceh Province with a high number of  hypertension sufferers. One of  the hypertension treatment  can be done by herbal treatment which is done by using antihypertension herbs. Mostly herbal treatment used to minimize the side effects of antihypertension drugs that are generally used for a long time. This study aims to analyze the dominant factors that influence the utilization of antihypertension herbs. The population of this study was 15.701 people and  99 of them were sample. The sampling technique was cluster random sampling .  The data were collected by using questionners which are designed for hypertension patients.  The dominant factor which affecting to utilize of antihypertension herbs was analyzed by using multiple logistic regression test with 95% confidence level. The results showed that  most of hypertension suffers in Langsa City choose starfruit as an antihypertension herbal plant (32%). There was a relationship between the knowledge level with the utilization of antihypertension herbs in Langsa City (p-value 0,001). There was also a significant relationship between the attitude level with the utilization of antihypertension herbs in Langsa City (p-value 0,000). Besides, the knowlegde level is the most utilization dominant factor  of antihypertension herbs (p-value 0,000).  After all, hypertension patients in Langsa City who have good knowledge level  9,834 times greater (rounded up to 10 times greates) tendency to use antihypertension herbal plants compared to patients with less knowledge level.